The Influence Of Work Discipline, Work Motivation, And Job Satisfaction On The Performance Of Village Office Employees In Seluma Sub-District, Seluma Regency - Beni Jekzen; Ida Anggriani; Nenden Restu Hidayah (Jurnal Ekonomi Islam, Akuntansi, dan Manajemen, 2026)
Employee performance is one of the important elements in an organization's success, especially in the context of public service that directly interacts with the community. Therefore, to achieve optimal performance, attention must be given to several influencing factors, such as work discipline, work motivation, and job satisfaction. The purpose of this study is to determine the Influence of Work Discipline, Work Motivation, and Job Satisfaction on the Performance of Village Office Employees in Seluma District, Seluma Regency. The data collection method in this study used a questionnaire technique, with a sample of 70 respondents. The results of the study show that the multiple linear regression equation is Y =-2.812 + 0.372X₁ + 0.511X₂ + 0.186X₃ + 1.495. The positive coefficients indicate a positive or unidirectional relationship between Work Discipline (X₁), Work Motivation (X₂), and Job Satisfaction (X₃) on Employee Performance (Y) in the village offices of Seluma Sub-District, Seluma Regency. The test results for work discipline (X₁) show a t-value of 2.704 > 1.668 and a significance level of 0.009 < 0.05, indicating that Hₐ is accepted and H₀ is rejected. This means that work discipline (X₁) has a positive and significant effect on employee performance. The test results for work motivation (X₂) show a t-value of 3.763 > 1.668 and a significance level of 0.000 < 0.05, indicating that Hₐ is accepted and H₀ is rejected, meaning that work motivation (X₂) has a positive and significant effect on employee performance. The test results for job satisfaction (X₃) show a t-value of 3.113 > 1.668 and a significance level of 0.003 < 0.05, indicating that Hₐ is accepted and H₀ is rejected, meaning that job satisfaction (X₃) has a positive and significant effect on employee performance. Based on the comparison of the F-count and the F-table value, Fcount is greater than Ftable (39.588 >2.51), leading to the conclusion that the hypothesis is accepted. This indicates a simultaneous effect of work discipline (X₁), work motivation (X₂), and job satisfaction (X₃) on employee performance (Y) in the village offices of Seluma Sub-District, Seluma Regency, as reflected in the significance level of 0.000 < 0.05.